Challenges with the use of postbiotics/parabiotics in food industry - Divsalar, Elahe; Incili, Gokhan Kursad; Shi, Ce; Semsari, Ehsan; Hosseini, Seyede Hanieh; Tirtashi, Fahimeh Ebrahimi; Moradi, Mehran (Taylor & Francis Inc, 2026)
The food industry is increasingly interested in postbiotics/parabiotics because of their ability to preserve and enhance functional food production. These substances contain several bioactive compounds with immune system-regulating, antimicrobial, antioxidant, prebiotic, and anticancer properties. Despite its potential benefits, incorporating postbiotics/parabiotics into food poses various obstacles that must be overcome. These include technical barriers in production, lack of uniform definitions and regulations, regulatory obstacles, limited consumer awareness and acceptance, quality control challenges, determining the most effective dosage, and cost considerations. This review discusses these challenges and the research progress that has been achieved to address these drawbacks. As research in this field continues to advance, addressing these challenges will be crucial to unlock the full potential of postbiotics/parabiotics in the food industry.
Keywords: Biotics; food preservation; functional food; marketing; regulatory aspects